Relationship Between Appraisal and Organizational Performance - Indradevi, R. (Prabandhan: Indian Journal of Management, 2012)
Performance appraisal processes are one of the central pillars of the performance management which is directly related to the organizational performance and have a direct impact on it. For an organization to be effective, the goals, the standards and the action plans need to be planned well in advance. Thus, performance appraisal facilitates the achievement of organizational goals. It also facilitates the optimal use of the organizational resources. It helps to identify and overcome the problems faced by the employees in their work. Performance appraisal is the strength of performance management, which in turn affects the organizational performance which triggered the author to make a study on the relationship between appraisal and organizational performance. The tool for the study was a questionnaire comprising of nine items on performance appraisal, seven items on employee capability and seven items on organizational performance on a five-point scale ranging from strongly agree (5) to strongly disagree (1). Data was collected from a sample of 125 respondents from five IT enabled companies in Chennai. Being satisfied with the reliability of the research instrument, the researcher carried out Pearson correlation and multiple regression to understand the relationship between appraisal and organizational performance.